Increasing Stability of Economy through Supply Chain Management and the Circular Economy - Marat Rashitovich Safiullin; Mikhail Valerievich Savelichev; Leonid Alekseevich Elshin; Vadim Olegovich Moiseev (International Journal of Supply Chain Management, 2020)
Abstract—This article presents preliminary propositions concerning implications for the development of what we term 'circular supply chains', defined here as the embodiment of circular economy principles within supply chain management. The economic system in the process of functioning generates positive and negative externalities. Currently, there are exacerbating problems associated with the need to minimize negative externalities, which pose global risks to the global economic system. The most acute risks are associated with ensuring the sustainability of financial systems, and also with environmental pollution, climate change, outbreaks of new types of deadly diseases. It seems promising to introduce elements of a circular economy, based on the use of non-waste technologies that minimize negative externalities. In addition, the solution to the problem of minimizing negative externalities within the framework of the current model of the economic system is associated with the creation of a mechanism for recording externalities and a mechanism for stimulating economic entities to minimize the negative external effects produced by their activities and maximize positive external effects. Tokenization on the supply chain platform creates the possibility of forming this mechanism. The system of tokenizing the externalies includes: (a) the formulation of the target behaviour of economic agents, (b) the creation of a supply chain platform that provides token issuance, (c) the determination of the exchange rate of tokens by economic agents for economic incentives (tax breaks, grants, investments, etc.), (d) an assessment of the effectiveness of economic agents in reducing negative externalities and increasing positive externalities.